Obtaining functional gradient coatings based on Al2O3 by detonation spraying - Б.К. Рахадилов; А.Б. Нугуманова; П. Ковалевский; М.К. Кылышканов; Л.Б. Баятанова; Д.Н. Какимжанов (Қарағанды университетінің хабаршысы. Физика сериясы)
The article deals with the phase composition and hardness of Al2O3 coatings obtained by detonation spraying. It was found that a decrease in the delay time between shots is leading to an increase in the hardness and elastic module of Al2O3 coatings. It was found based on X-ray diffraction analysis that the main reason for the increase in hardness with a decreasing in the delay time between shots is associated with increases in the volume fraction of α- Al2O3 phase. A high content of the more ductile γ-Al2O3 phase at the substrate-coating interface leads to an increase in adhesion characteristics, and a high content of the α-Al2O3 phase on the coating surface provides high hardness and wear resistance. The studies of X-ray diffraction presented that the highest phase content is achieved when the coatings are formed with a delay time between shots of 0.25 s. It was found that increase in the volume fraction of the α-Al2O3 phase is caused by the secondary recrystallization γ → α, which occurs due to the heating of particles during coating formation, i.e. due to increase in temperature above 1100 ºС in single spots of the coating when they are put each other.